Heavy physical exertion effect on functional indices of cardiovascular system under sharp reduction of high-qualification woman gymnasts' weight during competition period - Dorontsev, A. V.; Svetlichkina, A. A.; Zinchuk, N. A. (Proceedings of the First International Volga Region Conference on Economics, Humanities and Sports (FICEHS 2019), 2019)
A study on pronounced changes in haemodynamic indices under heavy physical exertion against short-period weight reduction was carried out among high-qualification woman gymnasts. As a rule, sharp weight reduction was observed among some of the gymnasts during the competition period, which allowed to detect significant reduction in reserve indices of the cardiovascular system, as well as the risk of pathological changes genesis under heavy physical exertion. According to the study, significant changes of the high-qualification gymnasts` cardiovascular system functional indices were observed when they lost 3-4 kg in weight several days prior to the competitions, with their own weight of 45-50 kg; when the weight reduction was softer - up to 1.5 kg per month - there were no pronounced changes in haemodynamic indices. The obtained results suggest removal of weight reduction stress methods, posing risks of organic changes of the cardiovascular system under heavy physical exertion, from rhythmic gymnastics training exercises.